Contribution of multivariate techniques to drought rates in understanding the otto-regions of the São Francisco basin (Research, Society and Development, 2021)
Objective: Use multivariate analysis techniques, in particular principal component analysis, to find the best description of drought rates, and then use cluster analysis to determine the homogeneous regions of the São Francisco River. Method: The indices to characterize the drought were calculated: Average annual maximum daily precipitation (annual max), annual average accumulated precipitation (amount), annual average of days without rain (